Ancient Africa, from Carthago to Aksum - (:unkn) unknown (My University, 2018)
This chapter presents the societies of Mediterranean North Africa, which gradually became part of the Roman Empire. The history of the kingdom of Meroe in the Hellenistic and modern periods is briefly discussed. The last part is devoted to East Africa and more particularly to the history of the kingdom of Aksum. The stateless societies (Blemmyes and Trogodytes) receive also special attention in this chapter.Translated with www.DeepL.com/Translator (free version)
Keywords: African Research